2015
DOI: 10.1016/j.devcel.2015.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Temporal-Spatial Resolution Fate Mapping Reveals Distinct Origins for Embryonic and Adult Microglia in Zebrafish

Abstract: Microglia are CNS resident macrophages, and they play important roles in neural development and function. Recent studies have suggested that murine microglia arise from a single source, the yolk sac (YS), yet these studies lack spatial resolution to define the bona fide source(s) for microglia. Here, using light-induced high temporal-spatial resolution fate mapping, we challenge this single-source view by showing that microglia in zebrafish arise from multiple sources. The embryonic/larval microglia originate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
171
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(181 citation statements)
references
References 65 publications
9
171
0
1
Order By: Relevance
“…2d). To more specifically label individual HSPCs, we adapted an hsp70l laser induction method that was used to trace microglial precursors in zebrafish 15 . At 48 hpf, there are only 10–15 cd41:eGFP + cells along the VDA 1,16 .…”
Section: Resultsmentioning
confidence: 99%
“…2d). To more specifically label individual HSPCs, we adapted an hsp70l laser induction method that was used to trace microglial precursors in zebrafish 15 . At 48 hpf, there are only 10–15 cd41:eGFP + cells along the VDA 1,16 .…”
Section: Resultsmentioning
confidence: 99%
“…However, later studies challenged this single source viewpoint by using temporal-spatial resolution fate mapping [48]. This study indicated that two different origins of microglia could be identified in zebrafish.…”
Section: Microglia Origins: From the Yolk Sac Or Non-yolk Sac Sources?mentioning
confidence: 99%
“…This process of sequential colonization of tissues by macrophages has also been observed during zebrafish development. However, in zebrafish, the brain continues to be colonized by new macrophages, resulting in the replacement of embryonic-derived microglia with adult-derived microglia [68]. In all other tissues examined in the murine embryo, macrophages derived from primitive hematopoiesis are replaced, or diluted, by macrophages derived from EMPs, or eventually, HSCs.…”
Section: Source Of Tissue-resident Macrophage Populations In the Fmentioning
confidence: 99%